2019
DOI: 10.1371/journal.pone.0221046
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure and construct validity of the parent-reported Inventory of Callous-Unemotional Traits among school-aged children and adolescents

Abstract: In this study, we assessed the factor structure and construct validity of the parent-reported Inventory of Callous-Unemotional Traits (ICU) among school-aged children and adolescents, aged 6 to 15 years, in a community setting in Japan (n = 10,936). We investigated 15 models that have been reported in previous studies and used confirmatory factor analyses to determine a model that might actually be the best-fit among these. We then examined the correlations between the score of ICU and the Strengths and Diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Nine samples reported that CU traits were significantly associated with indices of conduct problems ( d = 0.15–1.90), including delinquency (Fung et al, 2009; Li & Ang, 2019) and total aggression (Fung et al, 2009; Raine et al, 2014). This included two longitudinal studies that found that CU traits predicted later antisocial behavior (Hwang et al, 2020; Yoshida et al, 2019). Six studies, however, reported mixed or non-significant associations between CU traits and conduct problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine samples reported that CU traits were significantly associated with indices of conduct problems ( d = 0.15–1.90), including delinquency (Fung et al, 2009; Li & Ang, 2019) and total aggression (Fung et al, 2009; Raine et al, 2014). This included two longitudinal studies that found that CU traits predicted later antisocial behavior (Hwang et al, 2020; Yoshida et al, 2019). Six studies, however, reported mixed or non-significant associations between CU traits and conduct problems.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, Chu et al (2014) found no association between deviant peer affiliation and child CU traits. On the other hand, CU traits were found to be associated with peer problems (Yoshida et al, 2019). Additionally, callousness was associated with being a victim of physical bullying and a perpetrator of verbal/relational/physical bullying (Wang et al, 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…The ICU12 constitutes two intercorrelated factors, a 7-item Callousness factor where all items are standard-scored, e.g., “Shows no remorse when he/she has done something wrong,” and a 5-item Uncaring factor, where all items are reverse-scored, e.g., “Tries not to hurt others’ feelings.” Each item is rated on a 4-point scale, ranging from 0 (Not at all true) to 3 (Definitely true), and factor and total scores are the sum of the item responses. The ICU12 was developed using Item Response Theory analyses and research supports its use as a valid and brief measure of CU traits in both self- and parent-report versions ( Hawes et al, 2014 ; Colins et al, 2015 ; Pechorro et al, 2017 ; Yoshida et al, 2019 ; Thøgersen et al, 2020 ). Reliability was good for the total scale (α = 0.91), and acceptable for the Callousness (α = 0.88) and Uncaring (α = 0.81) subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this factorial structure has little support for the other-reported versions and in middle childhood ( Roose et al, 2010 ; Waller et al, 2015 ). Currently, a model with two correlated factors (Callous and Uncaring) is the most supported structure in the literature, with the number of items varying between authors ( Houghton et al, 2013 ; Hawes et al, 2014 ; Willoughby et al, 2015 ; Gao and Zhang, 2016 ; Yoshida et al, 2019 ). In particular, the ICU-12 by Hawes et al (2014) with 12 items and the ICU-11 ( Colins et al, 2016 ), which omits the only remaining item from the Unemotional factor from the ICU-12, are supported in various age periods such as in adults ( Wang et al, 2017 ), adolescents ( Zhang et al, 2019 ; Thøgersen et al, 2020 ; Allen et al, 2021 ), middle-aged children ( Hawes et al, 2014 ; Waller et al, 2015 ; Wang et al, 2020 ), in various cultures and with the self-reported or the other-reported versions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, item “Does not care who he or she hurts” and “Tries not to hurt others’ feelings” loaded on the Callous and the Uncaring subfactors, respectively ( Hawes et al, 2014 ). Therefore, the factorial structures which are supported the most by the current literature are not based on a clear theoretical background ( Ray et al, 2016a ; Yoshida et al, 2019 ) but are guided by statistical analyses. This constitutes an important limitation for the application of these structures in clinical settings, as the factors do not make sense at a theoretical level.…”
Section: Introductionmentioning
confidence: 99%